Comparison of the SenSmart™ and the INVOS™ neonatal cerebral near-infrared spectrometry devices - Wirayannawat, Wariphan; Amawat, Jutharat; Yamsiri, Nattaya; Paes, Bosco; Kitsommart, Ratchada (Frontiers in Pediatrics, 2023)
Objectives To determine the correlation and agreement between the SenSmart™ and the INVOS™ devices of neonatal cerebral regional oxygen saturation (CrSO2) measurements using neonatal sensors. The secondary objective was to develop a regression model that predicts CrSO2-INVOS values using CrSO2-SenSmart indices and determine whether the values between the devices are interchangeable. Methods A prospective, cross-sectional study was conducted in infants during the first 4 weeks of life. Simultaneous, bilateral CrSO2 was measured using the SenSmart™X100 (CrSO2-SenSmart) or INVOS™ 5100C (CrSO2-INVOS) device in each frontoparietal area for 2 h. Five-minute CrSO2 values were extracted for analysis. Results Thirty infants were recruited with 720 pairwise measurements and 26 (84%) were evaluated in the first week of life. Mean gestational age of the preterm and term infants was [30.9 ± 2.8 (n = 14) and 38.8 ± 1.1 (n = 16)] weeks, respectively. Overall CrSO2- was 77.08 ± 9.70% and 71.45 ± 12.74% for the SenSmart and INVOS, respectively (p < 0.001). The correlation coefficient (r) between the CrSO2-SenSmart and INVOS was 0.20 (p < 0.001). The mean difference between the CrSO2-SenSmart and INVOS was 5.63 ± 13.87% with −21.6% to 32.8% limits of agreement. The r and mean difference was 0.39 (p < 0.001) and 8.87 ± 12.58% in preterm infants, and 0.06 (p = 0.27) and 2.79 ± 14.34 in term infants. Conclusion The CrSO2-SenSmart tended to read higher than the CrSO2-INVOS device. There was no correlation between the CrSO2-SenSmart and the CrSO2-INVOS in term infants and it was weak in preterms. Due to imprecise agreement, the CrSO2-SenSmart values are not interchangeable with those of the CrSO2-INVOS.